KORELASI MOTIVASI BELAJAR DAN CARA BELAJAR DENGAN HASIL BELAJAR MATA DIKLAT KELISTRIKAN OTOMOTIF SISWA KELAS XI TEKNIK KENDARAAN RINGAN SMK PIRI 1 YOGYAKARTA TAHUN PELAJARAN 2013/2014 - Muhamad Nurdin; Tarto Sentono (Universitas Sarjanawiyata Tamansiswa, 2013)
Research purpose (1) to find out the correlation between learning motivation with the learning result of electrical automotive of students class XI Light Vehicle Engineering of SMK PIRI 1 Yogyakarta in the Academic Years 2013/2014, (2) to find out the correlation between the way of learn and the learning result of automotive electrical of students class XI Light Vehicle Engineering SMK PIRI 1 Yogyakarta in the Academic Years 2013/ 2014, (3) to find out the correlation between the learning motivation and the way of learning with the learning result of electrical automotive class XI of students class XI Light Vehicle Engineering SMK PIRI 1 Yogyakarta in the Academic Years 2013/ 2014.This researchâ€™s type is correlational and classified as ex post facto research. The population of this research is 97 students, the sampling technique used is saturated sample and population research. Data collection technique used is questionnaires and documentation technique. The Validity of each questions item acquired from the correlation of product moment. The reliability of the question is acquiredÂ with alpha formula. The data analysis technique used is simple regression and a double regression that previously conducted with prerequisite test analysis that are normality test, multi-correlation test, and linearity test.From the analysis result acquired the following research result: (1) there is positive correlation and significant between the motivation learning (X1) and learning result of automotive electrical (Y); there is positive correlation and significant between the way of learn (X2) and learning result of automotive electrical (Y); (3) there is positive correlation and significant among learning motivation (X1) and the way of learn (X2) with learning result of automotive electrical.Â